The Development in Contemporary Vocal Music Education in China - Qiwei, Duan; Pattananon, Nicha; Thanawat, Arthorn (Journal of Modern Learning Development, 2023)
China’s vocal music education culture has a history of thousands of years. Vocal music education plays an important role in controlling the development of vocal music culture, is entrusted with the human spiritual civilization, and the life of the laboring people is closely related. Of course, the development of culture is completely inseparable from the political and economic system, nor can it control the progress of human civilization. Vocal music culture is passed down through time, through the integration of knowledge by musicians of various nations, and then through the enrichment of human wisdom. It is developed according to its laws.